Pengaruh Kompos Dan Dosis The Kompos Terhadap Pertumbuhan Dan Hasil Sawi (Brassica JunceaL.) Di Lahan Kering Entisol. - ABUK, VERONIKA (Savana Cendana, 2025)
Abstrack 1Veronika Abuk. Effects of compost and a dose of compost tea on the growth and productivity of the mustard (Brassica juncea L.) in the dray land of entisol. Guided by 2.Eduardus Y. Neonbeni SP. MP and 3. Syprianus Ceunfin, SP., M. Sc. Thestudyaims to know theeffects ofcompost onthe growth and productivityofmustard plants (Brassicajuncea L.) and toknowhowadoseofcompostteaeffectgrowthand productivityof the mustard. Thestudywascarried out in September and October of2020in theoppositionofdaughterkimbana BTN, SouthBikomiDistrict,City Kefamenanu, North Central Timor (TTU). The research design used is a complete random design (CRD) oftwodistinctfactors.The first factorsisa compost consisting of thre cedars without compostascontrol,postfif teen ton/acresare, compost twenty five tons/acres are. Thesecondfactoris a three-arasdoseofcompostandcompostteatwo, compostfivemillits.The observedvariable compost tea in general donot showthe effect ofinteractions on all observations.The sole impactofcompost measure twentyfive tons/acres are shows fresh,non-econimical data of the tallest plant real difference between the cedar’streatment. Compostteatwo,fivemilli compost effects optimally increases growth and produce plants that are properlyexpressing with the freshet weigth of the tallest tatal plant, the higthest fresh weight. Keywords: (Brassicajuncea L.)compost and a dose of compost tea